(untitled) (Palimpsesto, 2017)
This paper analyses the process of transformation of the political identities of a fraction of the Argentinian intellectual left that edited the Journal Controversia. Para el examen de la realidad argentina (1979-1981) during their Mexican exile, and the influence that the contact with intellectuals from other latitudes had in such transformation. The hypothesis is that the role played by universities, regional centers of investigation and journals as well as the new forms of debates that emerged as a result of the confluence of latinamericans in Mexico, produced a “latinamericanization” of these intellectual’s thoughts that left a mark in the process of renovation.